2020
DOI: 10.1080/19476337.2020.1767694
|View full text |Cite
|
Sign up to set email alerts
|

Influence of enzymatic hydrolysis conditions on biochemical and antioxidant properties of pacific thread herring (Ophistonema libertate) hydrolysates

Abstract: Pacific thread herring (Ophistonema libertate) muscle was hydrolyzed with Alcalase for the preparation of protein hydrolysates. The effect of enzyme concentration (EC; 1% and 3%), pH (8 and 9) and temperature (40°C and 50°C) on some biochemical properties and antioxidant activity (AOXA) was determined. The degree of hydrolysis (DH) ranged between 9.6% and 33.1%. The highest DH was obtained with the following conditons: EC of 3%, pH 9 and temperature of 50°C; however, the highest AOXA measured by DPPH (183.7 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The protein hydrolysates were prepared using centrifuged sardine stickwater (CSW) and Alcalase ® 2.4L (E.C. 3.4.21.62, subtilisin A from Bacillus licheniformis; Sigma-Aldrich P4860; St. Louis, MO, USA) as protein substrate and enzyme source, respectively, following the method described by Sandoval-Gallardo et al [14]. In brief, an appropriated sample of CSW to obtain 25 g of crude protein was dissolved with distilled water in a thermo regulated reaction vessel.…”
Section: Production Of Protein Hydrolysatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein hydrolysates were prepared using centrifuged sardine stickwater (CSW) and Alcalase ® 2.4L (E.C. 3.4.21.62, subtilisin A from Bacillus licheniformis; Sigma-Aldrich P4860; St. Louis, MO, USA) as protein substrate and enzyme source, respectively, following the method described by Sandoval-Gallardo et al [14]. In brief, an appropriated sample of CSW to obtain 25 g of crude protein was dissolved with distilled water in a thermo regulated reaction vessel.…”
Section: Production Of Protein Hydrolysatesmentioning
confidence: 99%
“…Although the Paci c thread herring is one of the small pelagic species of highest importance in shmeal production in terms of catch volume, and even the usage of their muscle to produce protein hydrolysates has been explored [14], the information related to the use of Paci c thread herring stickwater as raw material to obtain bioactive compounds is scarce. Designing a suitable treatment process to recover and add value to stickwater e uents would be highly bene cial.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several physical and chemical factors, such as temperature and enzyme concentration, may influence the relationship between enzyme activity and enzyme concentration. The moderate increase in temperature can improve the effectiveness of the enzyme–substrate interaction due to an exposure of H 2 bonds to proteases, as a result, the extraction is more efficient (Sandoval‐Gallardo et al ., 2020). Based on these findings, the hydrolysis temperature of 50 °C and enzyme concentration of 7 U mL −1 resulted in the increased yield of total free amino acids and ACE inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…The DPPH radical scavenging potential of the protein hydrolysates, was analysed according to Müller et al (2011), with slight modifications, reported by Sandoval‐Gallardo et al (2020). The percentage of DPPH radical scavenging was calculated according to the following equation:DPPH scavenging0.25em)(%goodbreak=1ABS0.25emsampleABS0.25emcontrolgoodbreak×100The trolox equivalent antioxidant activity was expressed in μmol of Trolox Equivalent (TE) per mg of dry sample.…”
Section: Methodsmentioning
confidence: 99%
“…The Pacific thread herring ( Ophistonema libertate ), is one of the small pelagic species with the greatest commercial importance in terms of catch volume and represents one of the most important fisheries in north‐western Mexico (Ruiz‐Domínguez & Quiñonez‐Velázquez, 2018). This resource is used mainly in the production of fishmeal and fish oil; however, the high‐quality muscle protein of these pelagic fish in terms of content of essential amino acids and digestible compounds, is considered as a quality raw material, which can be used to produce high value commercial products, such as protein hydrolysates (PH; Sandoval‐Gallardo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%